Simulation of Surface Potential Distribution Induced by Electronic Carrier Injection into Single Silicon Quantum Dot - Yudi Darma; Rizal Kurniadi; M. Hamzah Fauzi; Yuli Cha Tarido (Indonesian Journal of Physics, 2006)
In this paper we propose a numerical simulation method of the surface potential distribution based on the solution of two-dimensional Poisson equation in rectangular coordinates with boundary condition. The simulation results confirm that the surface potential changes on the dot by electron injection and/or extraction, in contrast to the neutral dot in which just a flat potential image was observed. . In this work we investigated the charge states of individual quantum dot with the diameter of 10 and 20nm. Note that, if two or more electrons are injected/extracted to/from the quantum dot, the coulombic repulsion effect is observed, and more clearly for the dot with the bigger size due to the charges separation into the quantum dot.